Impact of rhizosphere quantitative microbiome and soil properties on alkaloid levels in Lycoris aurea herb - Guang-hua Liu; Jianglin Li; Long-Xia Yan; Hong-Ping Deng; Miao-Hua Quan; You-Wei Zuo (Scientific Reports)
Abstract Lycoris aurea Herb is a plant renowned for its striking appearance and medicinal properties, particularly the production of alkaloids such as lycorine and galanthamine, which have therapeutic potential in treating diseases. Understanding the interaction between L. aurea and its rhizosphere microbiome is crucial, as the microbiome influences plant health, nutrient availability, and metabolite biosynthesis. This study investigated the interplay between rhizosphere microbiome and alkaloid levels in L. aurea using genetically identical plant samples collected from two ecologically distinct regions. The findings revealed that higher levels of lycorine and galanthamine correlated with specific soil physicochemical properties such as higher acid phosphatase activity and higher sodium and manganese levels. Additionally, quantitative Accu16STM and AccuITSTM sequencing demonstrated distinct bacterial and fungal diversities in the high alkaloids-producing group compared with the low alkaloids-producing group. Our study found that the abundance of four dominant bacterial phyla Acidobacteriota, Proteobacteria, Actinobacteriota, and Planctomycetota was higher in the low-alkaloid content group, whereas the dominant fungal phylum Ascomycota was more abundant in the high-alkaloid content group. Linear discriminant analysis revealed distinct variations in bacterial and fungal taxa, with the high-alkaloid content group containing ten bacterial indicators, such as Kitasatospora and Acidimicrobiaceae, and ten fungal taxa, including Boletales, Vandijckomycella and Sclerodermataceae. Functional annotations of microbial taxa revealed differences in metabolic functions such as chitinolysis and nitrate reduction in the high alkaloid groups, respectively. Moreover, Spearman correlation analysis underscored the relationships between microbial diversity and soil characteristics, particularly emphasizing the role of soil pH in influencing microbial populations. In conclusion, this research provides valuable insights into the environmental and rhizosphere microbial dynamics of L. aurea, offering implications for alkaloid biosynthesis and pharmacology.